The Conflicts of the Main Character in â€œThe Sound of Musicâ€ - Harijanto, Karissa Mitha (Journal of English Department WM, 2013)
Most people enjoy watching films. One of the films that teaches a lot of life lessons is The Sound of Music, a legendary musical film that was made in 1965. In this thesis, the writer analyzes the main character in the film, Maria von Trapp, as the focus of the study. The objective of the study is to find out the conflicts that happen to Maria, the possible causes of the conflicts, how Maria manages the conflicts, and the effects of Mariaâ€™s presence in the von Trapp family. The analysis found that Maria faced two internal and four external conflicts. The possible causes of the conflicts came from both outside and inside Maria herself. However, Maria managed the conflict quite well with a little help from the Reverend Mother. Maria brought significant changes to the von Trapp family. She made the von Trapp family, who had been so stiff and gloomy since the death of the mother, happy and warm again.